Improved system for Butterfly Valve - Harikrishnan, AR; Jishnu,; Leneesh N, Gopal; Jose, Arun (International Journal of Computer Sciences and Engineering, 2025)
A cost-effective procedure to surface alloy WCB steel butterfly valve sand castings using mold coatings incorporating metal and ferroalloy powders has been described.The tooling, mold design, and casting conditions similar top lain WCB castings were successfully used to produce sound surface alloyed butterfly castings under industrialconditions. The dynamic behaviour control of a butterfly valve is important because , when one of the valve disc natural frequency is close to the frequency of vortex shedding, which appears when the valve is fully open or partially closed, resonance may appear and vibration with significant amplitudes is generated.The surface alloying was achieved by addingpowders of Ni, Cr, Fe–Si, Fe–Mn, and Mo to the slurrycontaining a binder coated on the mold surface. The sur-face alloyed coatings on the surface of WCB steel butterfly valve castings were enriched in Ni, Cr, Mo, and Mn up to 6.4, 23.2, 3.3, and 1.1%, respectively. The depths of coatings were as high as 420 lm. After normalizing and tempering heat treatment, the surface alloyed layer exhibitedan increase in corrosion resistance as compared to base metal WCB steel.